Search for collective behavior in very small and in large systems - Padula, Sandra S. [UNESP] (My University, 2025)
Signs of collectivity were initially seen in AuAu collisions at RHIC through measurements of two-particle long-range correlations in (pseudorapidity) Δη, within small (azimuthal) Δφ angles. In 2010 a similar ridge-like behavior was observed in high multiplicity pp collisions at 7 TeV at the LHC by CMS, extended afterwards also to pPb and PbPb collisions. In addition, several orders of anisotropic flow Fourier harmonics were measured later, showing a collective behavior compatible with hydrodynamic expectations. This posed the question about the threshold on system size and conditions for collectivity to arise. Signs of possible collectivity were then searched for in e+e− and ep at LEP, in γp and γA at the LHC, but usually limited to lower multiplicity ranges (< 40 particles per event), where collectivity was not expected, with negative results. However, more recent investigations with higher multiplicity data collected with the ALEPH experiment at LEP II energies seem to indicate a different picture. This talk shows recent results from the CMS Collaboration for two extreme sizes of colliding systems. On the lowest side, the results focus on the search for a ridge-like behavior in high multiplicity pp collisions at 13 TeV inside a single jet, originated from a highly energetic parton. On the other extreme, PbPb collisions at √sNN = 5.02 TeV are employed to probe deeper into the quark-gluon plasma formed in such collisions, by measuring the speed of sound and the effective temperature in this medium.